Buddhism and Personality. A mixed qualitative-quantitative study about Soka Gakkai International from Uruguay. - Apud, Ismael (2023)
The present research focuses on the effects of Buddhist practice (daimoku), community belongingness, and beliefs on the personality and subjective temporality of members of Soka Gakkai International in Uruguay. We used a mixed quantitativequalitative design, which included the application of the Zuckerman-Kuhlman-Aluja Personality Questionnaire/Short-Form and the Dark Future Scale psychometric scales and qualitative in-depth interviews. The sample consisted of 22 subjects who, compared to a control group, showed: i. significantly lower scores with a mediumsized effect for the neuroticism-anxiety trait and each of its facets (anxiety, depression, dependence, and low self-esteem) and for the aggressiveness-hostility trait and its facet verbal aggression; ii. significantly higher scores and medium effect size for the sociability-extraversion trait and its positive emotions and social warmth facets, and for the general activity facet; and iii. significantly lower scores and a large-sized effect for future anxiety. In-depth interviews reveal a high valuation of daimoku practice as promoting positive changes in self-esteem, anxiety, mood, sociability, activity, and subjective temporality. Buddhist beliefs and community were also positively valued.